A COMPARATIVE STUDY OF AUTOLOGOUS BLOOD VERSUS CONVENTIONAL CONJUNCTIVAL AUTOGRAFT SURGERY FOR PTERYGIUM - Mandal, Govind Kumar; Choudhary, Jagdish; Roy, Pummy (Student’s Journal of Health Research Africa, 2024)
Background Pterygium is a common ocular condition characterized by fibrovascular conjunctival tissue growth onto the cornea. Surgical excision and conjunctival autografting are the main treatments to reduce recurrence. The use of autologous blood (AB) as a graft adhesive has become more popular due to its cost-effectiveness, shorter surgical time, and elimination of extraneous materials. Objective: To compare autologous blood graft fixation’s efficacy, safety, and recurrence rates to conventional suture fixation in conjunctival autograft surgery for primary pterygium. Methods A 13-month prospective, comparative study was conducted at Jawahar Lal Nehru Medical College and Hospital in Bhagalpur. The 127 primary nasal pterygium patients were divided into two groups: Group A (n=64): Autologous blood graft adhesion. Traditional 8-0 Vicryl suturing (Group B, n=63). All procedures were performed under local anesthesia by the same surgeon. After surgery, patients were monitored on days 1, 7, 30, 90, and 180. The parameters assessed included operation duration, postoperative pain, graft stability, complication rates, and recurrence (≥1 mm fibrovascular regrowth into the cornea). Results The average operating duration was significantly shorter in Group A (18.5 ± 3.2 minutes) compared to Group B (30.2 ± 4.1 minutes; p<0.001). Group A had significantly less postoperative pain and erythema in the first week. Graft displacement occurred in 4.6% of Group A and 0% in Group B (p<0.05). Three patients (4.6%) in Group A and two (3.1%) in Group B had recurrence at six months, which was not statistically significant (p>0.05). Conclusion Autologous blood is a safe, effective, and cost-effective alternative to sutures for fixing conjunctival autografts in primary pterygium. It significantly reduces surgery time and postoperative pain. Graft displacement is slightly more likely, but proper surgical technique can reduce it. Both procedures have similar recurrence rates, suggesting autologous blood is a viable alternative in high-volume, resource-constrained ophthalmology.